Mengoptimalkan Formulasi Pakan Ikan: Meningkatkan Kandungan Protein Dengan Menggunakan Ikan ‘Sapu-Sapu’ Sebagai Bahan Baku Industri Perikanan - Arief Hardi Rahman; Wahyu Adila Pratama; Siti Sahara (Jurnal Ilmiah Global Education, 2024)
The decrease in production and the rise in the price of protein feed haveincreased costs and financial pressure on fish farmers. Data from theMinistry of Marine Affairs and Fisheries shows production costs have risenby 2.13%. This research aims to provide an alternative to high-protein feedby using suckermouth catfish as an ingredient. The study uses a Researchand Development approach with a 4-D model (define, design, develop,disseminate). The sample includes two catfish per participant. Data wascollected through monitoring, questionnaires, and expert reviews, using afour-point Likert scale. Results indicate 60% of volunteers observedincreased fish growth, 66.7% stated fish health was very good, and 53.3%reported increased feed consumption. However, 66.7% of volunteers ratedwater quality as poor. Despite this, 60% rated the physical and nutritionalquality of the alternative feed as good, and 53.3% rated the benefits andcost as very good. In conclusion, using suckermouth catfish as analternative feed ingredient can reduce feed costs and improve catfishgrowth and health, though water quality management needsimprovement. These findings offer hope for fish farmers to tackle risingfeed prices with a more affordable and sustainable solution.